Preparation, characterization, and mechanistic analysis of BiVO4/CaIn2S4 hybrids that photocatalyze NO removal under visible light. (November 2018) - Wan, Shipeng; Ou, Man; Cai, Wei; Zhang, Shule; Zhong, Qin
Abstract: In this study, BiVO4 /CaIn2 S4 hybrids were prepared with a facile impregnation method. The synthetic materials were characterized by several techniques, including X-ray diffraction, X-ray photoelectron spectroscopy, electron spin resonance (EPR), photoluminescence (PL) spectroscopy, scanning electron microscopy, and ultraviolet–visible diffuse reflectance spectroscopy. The photocatalytic abilities of the BiVO4 /CaIn2 S4 hybrids were evaluated based on the oxidation of NO in the presence of a low level of H2 O2 . The photocatalytic performance of the hybrids was improved compared with BiVO4 and CaIn2 S4, and the highest photocatalytic activity reached 80.16%. The excellent photocatalytic performance was mainly due to the strong oxidation/reduction ability of holes/electrons, the masses of active radicals, and the rapid separation of photoinduced carriers according to the PL spectra. The product was NO3 − based on Fourier transform-infrared analysis and ion chromatography. A trapping experiment and EPR suggested that ·OH and ·O2 − had significant effects on NO removal. Finally, we propose a Z-scheme photocatalytic mechanism for NO removal with the BiVO4 /CaIn2 S4 hybrids. Graphical abstract: Image 1 Highlights: Z-scheme BiVO4 /CaIn2 S4 photocatalyst synthesized by facile impregnation method. NO conversion in presence of BiVO4 /CaIn2 S4 photocatalyst reached 80.16%. Excellent photocatalytic performance of the composites was analyzed. Oxidation mechanism of NO and related active species were studied.